Barriers to and determinants of medication adherence among hypertensive patients attended National Health Service Hospital, Sunderland - Muhammad Umair Khan; Shahjahan Shah; Tahir Hameed (Wolters Kluwer Medknow Publications, 2014)
Background: Hypertension is a silent killer, a time bomb in both the developed and developing nations of the world. It is one of the most significant risk factors for cardiovascular morbidity and mortality resulting from target-organ damage to blood vessels in the heart, brain, kidney and eyes. Adherence to long-term therapy for chronic illnesses like hypertension is an important tool to enhance the effectiveness of pharmacotherapy. Objective: The two objectives of this study were to evaluate the extent and reasons of non-adherence in patients attended National Health Service (NHS) Hospital, Sunderland. Materials and Methods: The study was conducted for 4 months in the out-patient department of NHS Hospital. A total of 200 patients were selected randomly for this study. Morisky's Medication Adherence Scale was used to assess the adherence rate and the reason of non-adherence. Data were entered and analyzed using Microsoft Excel 2010. Results: The overall adherence rate was found to be 79% (n = 158). Adherence rate in females were low was compared with their male counterparts (74.7% vs. 85.7%). The higher rate of adherence was found in age group of 30-40 years (82%, n = 64). The major intentional and non-intentional reason of non-adherence was side-effects and forgetfulness respectively. Conclusion: Overall, more than three-fourth of the hypertensive participants were found to be adherent to their treatment. On the basis of factors associated with non-adherence, it is analyzed that suitable therapy must be designed for patients individually to increase medication adherence and its effectiveness.